2019
DOI: 10.1093/mnras/stz2596
|View full text |Cite
|
Sign up to set email alerts
|

The SLUGGS survey: measuring globular cluster ages using both photometry and spectroscopy

Abstract: Globular cluster ages provide both an important test of models of globular cluster formation and a powerful method to constrain the assembly history of galaxies. Unfortunately, measuring the ages of unresolved old stellar populations has proven challenging. Here, we present a novel technique that combines optical photometry with metallicity constraints from near-infrared spectroscopy in order to measure ages. After testing the method on globular clusters in the Milky Way and its satellite galaxies, we apply ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 230 publications
(381 reference statements)
9
45
1
3
Order By: Relevance
“…The analysis showed that the Milky Way experienced a total of ∼ 15 mergers throughout its history, with the last major merger having taken place at z > 4, thus sharpening previous limits of z > 2 (e.g., Wyse 2001;Hammer et al 2007;Stewart et al 2008). Improved determinations of the ages of extragalactic GCs may enable the application of these correlations to galaxies beyond the Milky Way in the near future (Usher et al 2019). In addition, the analysis presented by predicted the existence of the satellite Gaia-Enceladus/Sausage (GES), which was discovered only weeks later in the data from Gaia's second data release (e.g., Myeong et al 2018;Helmi et al 2018), as well as the enigmatic galaxy Kraken, which together with the GES accretion event forms the two most massive galaxies ever accreted by the Milky Way.…”
Section: Cluster Populations As Tracers Of Galaxy Assemblymentioning
confidence: 92%
“…The analysis showed that the Milky Way experienced a total of ∼ 15 mergers throughout its history, with the last major merger having taken place at z > 4, thus sharpening previous limits of z > 2 (e.g., Wyse 2001;Hammer et al 2007;Stewart et al 2008). Improved determinations of the ages of extragalactic GCs may enable the application of these correlations to galaxies beyond the Milky Way in the near future (Usher et al 2019). In addition, the analysis presented by predicted the existence of the satellite Gaia-Enceladus/Sausage (GES), which was discovered only weeks later in the data from Gaia's second data release (e.g., Myeong et al 2018;Helmi et al 2018), as well as the enigmatic galaxy Kraken, which together with the GES accretion event forms the two most massive galaxies ever accreted by the Milky Way.…”
Section: Cluster Populations As Tracers Of Galaxy Assemblymentioning
confidence: 92%
“…This limits the sample of galaxies with accurate GC population ages to a the Local Group, which may bias our observational picture of when the 'typical' GC forms. Observations of nearby early-type galaxies suggest that they may contain a younger GC population compared to the MW (Usher et al 2019).…”
Section: Comparison To Observationsmentioning
confidence: 99%
“…Otherwise, the GC ages have typical random uncertainties of > 2 Gyr, reflecting the challenging age determination of old stellar populations (e.g. Usher et al 2019, or App. in Fahrion et al 2019b.…”
Section: Globular Cluster Agesmentioning
confidence: 99%